Islam, Arsip, dan Arsipelago - Umam, Zacky Khairul (Masyarakat Sejarawan Indonesia, 2017)
The term arsipelago or â€œarchivelagoâ€ in this paper literally means the assemblage of plural archives which have their contextual foundation, i.e. geographical significance in Indonesia as an archipelagic cultural sphere. Its chief principle connects to the value of diversity as revealed by the manifests of a variety of cultural expression. The principle cognates with the nature of archival survival in the country. There is no single island of an archive, but there are imaginative islands of archives. The tendency to fold archive as monotonous through the series of political repercussion should be provincialized, as the polyphonic voices of the arsipelago unfold the untold narratives of people. Within this articulation, archives related to Islam(s) and Muslims in Indonesia have to be rediscovered, after the long period of negation, partly because of the symbiosis between late colonial legacy and the perpetual ignorance of Indonesian elites to value archive as power/knowledge.